The Effectiveness of Cahaya Terampil Scholarship Distribution by Yayasan Baitul Mal PLN UP3 North Sumatra: An Islamic Economics Perspective - M. Luthfi Perdana siregar; Muhammad syahbudi; Ahmad Muhaisin (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Higher education is not merely about obtaining degrees but also about empowering individuals to contribute meaningfully to society. Financial support, such as the Cahaya Terampil Scholarship from YBM PLN UP3 North Sumatra, plays a crucial role in achieving this goal, particularly for underprivileged students. This article aims to analyze the effectiveness of the Cahaya Terampil Scholarship distribution in addressing the financial challenges faced by mustahiq (eligible recipients) in Medan. The study utilizes a qualitative approach, analyzing secondary data on the distribution of scholarship funds. Findings indicate that the distribution of scholarships has declined from January 2023 to July 2024, and its effectiveness has diminished over time. From an Islamic economic perspective, this inefficiency highlights the need for improved management and socialization strategies to enhance the impact of zakat-based scholarship programs. The research contributes to efforts to improve access to higher education for underprivileged students, reinforcing the principles of justice and welfare in Islamic economics.